Are We Missing the Forest for the Trees? Quantifying the Maintenance of Diversity in Temperate Deciduous Forests - (:unkn) unknown (My University, 2016)
One of the most pressing questions of community ecology is: Why do we have so many species? Over 100 hypotheses have been proposed to answer this question for woody plants over the past 70 years, yet there remains no consensus among community ecologists. In this dissertation, I explore the evidence supporting several different hypotheses (Chapter 1). I provide evidence that negative density dependence, where individuals perform poorly near members of their own species, may only be relevant for canopy tree species (Chapter 2). Understory species do not demonstrate negative density dependence while canopy trees demonstrate negative density dependence that increases with plant size as predicted. Furthermore, I examine the effect that disturbance and herbivory by large vertebrate herbivores have on negative density dependence in a fully-factorial experiment. I found that disturbance overrides negative density dependence and enhances diversity by 60% while herbivory strengthens negative density dependence (Chapter 3). These findings suggest that even where negative density dependence is present, it is modulated by disturbance. I also explore the life-history strategies that determine the interplay between these mechanisms. Shade-tolerance, an important life history trade-off spectrum in temperate plants, did not significantly influence which mechanisms were relevant for diversity maintenance. Conversely, whether a plant was in the canopy or in the understory, a coarse metric that combines many trade-off spectra, was a good predictor of both the strength of negative density dependence and the effect of disturbance (Chapter 4). Understory plants demonstrated strong spatial clustering while canopy trees demonstrated strong negative density dependence. Disturbance randomized the spatial patterns of both understory and canopy plants.
Keywords: Community Ecology; Deciduous Forests; Diversity Maintenance; Negative Density Dependence; Plant Ecology; Point Pattern Analysis